Intake Valve Modelling Of A Four Stroke Internal Combustion Engine At Idling Speed - Molla, Md.Syed Ali (2002)

(untitled)
Intake valve of a four stroke internal combustion (IC) engine has been modelled to investigate the effects of intake valve diameter and intake valve angle on volumetric efficiency and air flow properties of intake air in a four stroke internal combustion engine. It is found that the increase of intake valve diameter increases the peak vertical velocity component but decreases the peak horizontal velocity component of intake air in suction stroke. It is also found that the increase of intake valve diameter decreases the peak turbulence kinetic energy and dissipation rate of intake air to a small extent. The effects of intake valve diameters on the cylinder pressure in suction stroke become significant from the suction valve full opening timing to the middle of suction stroke but its effects become insignificant (diminished) at the time of suction valve closing. The effects of intake valve diameters on the intake air temperature are also found very small at the end suction stroke. Thus, the small variations between the computed pressure and temperature inside the cylinder at end of suction stroke for different intake valve diameters have little influence on volumetric efficiency. While investigating the effect of intake valve angle on the airflow properties, it is found that the larger intake valve angle decreases the vertical velocity component as well as the horizontal velocity component. The increase of intake valve angle decreases the turbulence kinetic energy and dissipation rate moderately. The effects of intake valve angles on the cylinder pressure and temperature in suction stroke are very small from intake valve opening timing until the end of suction stroke. Thus, the present investigation shows that variation in intake valve diameter has very small effect on volumetric efficiency and the necessity of increasing intake valve number is not so important. Moreover, intake valve angle can be increased in order to increase valve thickness and valve life.